ОЦІНКА ЕФЕКТИВНОЇ ШВИДКОСТІ ПЕРЕДАЧІ ІНФОРМАЦІЇ ДЛЯ КАНАЛУ СТАНДАРТУ 802.11n У ДІАПАЗОНІ 5ГГц (World Science, 2016)
Investigation of temporal characteristics of the effective speed of transfer information in the frequency range of 5 GHz for the wireless channel of 802.11n standard was conducted in this work. It is a basic parameter of the quality of wireless networks which is affected by several factors: fluctuation of wireless channel parameters during the transmission in time; obstacles which are independent sources of the emission; architectural obstacles.Based on experimental studies of temporal characteristics of the effective speed it was concluded that there are quite high fluctuations of values up to 10 Mbit/s on the line of sight which decrease with increasing density and thickness of architectural obstacles.